VOICE ENABLE PERSONALIZED WEB SEARCH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The technology of voice browsing is rapidly evolving these days. It is because the use of cell phones is increasing at a very high rate, as compared to connected PCs. Speech interface integrated browser is a web browser that helps users by using an interactive voice user interface ,useful to those who have difficulties in seeing and reading a web content. Listening and speaking are the natural modes of communication and information gathering. As a result we are now heading towards a more voice based approach of browsing rather than operating on textual mode. A voice browser or speech browser will take and presents the information in the form of voice as well as text, using text to speech and speech to text conversion to render information. People want to get accurate and appropriate data at the top of search results in a user friendly manner. People also want to get a personal space over the internet when they are browsing on web, from this arises a need of personalization of the search history. Thus there is a need of a highly efficient and effective ranking algorithm that provides search results according to user preferences. This paper concentrates on this new technique, voice browsing, which unites speech recognition and speech synthesis with better personalized search that can be very fruitful in the coming years. In this paper we provide personalization by creating individual search history for each user on the browser and also focused on the search results to get customized according to the user demand.